THE VALUE OF PROCUREMENT TO AN ORGANISATION - Bulbeck, Emily (The journal of contemporary issues in business and government, 2010)
As the strategic potential of procurement has been explored by academics and professionals, there has been increasing discussion surrounding the ways that procurement can be of value to an organisation. Theories of competitive advantage are discussed as one method for procurement to add value. In this paper the major types of competitive advantage – cost leadership and differentiation – are outlined and the importance of procurement’s alignment with overall corporate strategy for achieving a competitive advantage is stressed. Three procurement strategies – operational improvement, supply chain collaboration and sustainable purchasing – are discussed as further examples of how procurement can create a competitive advantage for an organisation. The discussion highlights three complications that surround determining the value of the competitive advantage: indirect relationships, implementation gaps and measurement. Conclusions drawn from this discussion indicate that these complications are common to all strategies discussed. Despite the complications in determining the value of competitive advantage, it is shown to be an important way that procurement can be valuable to an organisation.